Using PhET Interactive Simulations to Improve the Learners’ Performance in Science - Dy, Abbie U.; Lagura, Jessel C.; Baluyos, Genelyn R. (PT ARRUS Intelektual Indonesia, 2024)
In the science section of the 2018 Programme for International Student Assessment (PISA), the Philippines came in last out of all the participating countries. Through a classroom-based research methodology, the study aimed to determine the effectiveness of using Physics Education Technology (PhET) to enhance learners' performance in science in grade 10. Thirty-three pupils from a public school in Ozamiz City were chosen by purposive sampling in the academic year 2023–2024. Both qualitative and quantitative approaches were used in the study; data were gathered through interviews and a test created by the researcher. To understand the results thoroughly, statistical analysis was conducted using Minitab and HyperResearch, utilizing methods such as mean, standard deviation, t-test, and theme analysis. The study aimed to achieve the following objectives: Determine the learners’ performance before using PhET interactive simulations; Determine the learners’ performance before using PhET interactive simulations; Identify significant difference in learners' performance before and after using PhET interactive simulation; and explore other observed developments among the learners after the use of PhET interactive simulation. The findings revealed an outstanding improvement in the learners’ overall performance following the integration of PhET interactive simulations into science learning. Therefore, the PhET interactive is an effective tool for improving the learners’ performance in science. This supports a recommendation that PhET simulations can be effectively incorporated to enhance students' understanding of scientific concepts.